2005
DOI: 10.14712/18059694.2018.35
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Role of Urinary N-Acetyl-β-D-glucosaminidase (NAG) Activity in the Detection of Renal Tubular Impairment

Abstract: The kidney function can be assessed by a number of methods. The urinary excretion of enzymes, in particular N-acetyl-β-D-glucosaminidase (NAG), is considered a relatively simple, cheap, fast and non-invasive method in the detection and follow-up of renal tubular function under various conditions. The determination of urinary NAG provides a very sensitive and reliable indicator of renal damage, such as injury or dysfunction due to diabetes mellitus, nephrotic syndrome, inflammation, vesicoureteral reflux, urina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
83
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 69 publications
5
83
1
2
Order By: Relevance
“…Urinary NAG was significantly elevated in the MHRS model in the present study reflecting tubular dysfunction and kidney parenchymal damage as reported by Skálová (2005). In agreement with this result, high urinary NAG was reported in infants with liver cirrhosis (Aydogdu et al, 2004) pointing to an occurrence of renal dysfunction and HRS.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Urinary NAG was significantly elevated in the MHRS model in the present study reflecting tubular dysfunction and kidney parenchymal damage as reported by Skálová (2005). In agreement with this result, high urinary NAG was reported in infants with liver cirrhosis (Aydogdu et al, 2004) pointing to an occurrence of renal dysfunction and HRS.…”
Section: Discussionsupporting
confidence: 92%
“…The increased plasma creatinine and reduced creatinine clearance in MHRS in the present study reflected that glomerular function, proximal tubules and glomerular filtration rate are affected in HRS as reported previously (Van Lente and Sult, 1989;Skálová, 2005). Renal dysfunction in patients with cirrhosis with superimposed inflammation was reported previously to be associated with significant tubular injury (Shah et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…The urinary content of another lysosomal enzyme, N-acetyl-␤-glucosaminidase, also known as ␤-hexosaminidase (130 kDa), is routinely used as a clinical marker for early detection of renal tubular impairment in glomerular disease (21) and is generally regarded as reflecting release from PTC. We propose to reassess the significance and usefulness of this assay.…”
Section: Discussionmentioning
confidence: 99%
“…1 With a molecular mass of 130-140 kDa, circulating NAG is not filtered through the glomeruli. In the kidneys, NAG is found predominantly in lysosomes of proximal tubular cells, and the small amount of NAG normally present in the urine is secreted by these cells by exocytosis.…”
mentioning
confidence: 99%